Evaluasi Penggunaan Obat Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisis Di Rsud Toto Kabila Periode 2017-2018 - Teti Sutriyati Tuloli; Madania Madania; Moh Adam Mustapa; Evania P. Tuli (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Chronic Renal Failure (CRF) is kidney damage with a decrease in Glomerular Filtration Rate (LFG) of less than 60mL/min/1.73 m2 during (at least) 3 months. Hemodialysis therapy is the most widely used CRF therapy. Due to certain conditions, in addition to receiving hemodialysis therapy, patients with CRF alsoreceive oral drug therapy. This is intended to overcome complications both from CRF and hemodialysis therapy itself. This study aims to evaluate drugs use in patients with CRF with hemodialysis based on four aspects, namely the proper patient, the proper medication, the proper indication and the proper dose according to the standard of therapy. This research was a descriptive study using a cross sectional design with data collection done retrospectively on patients undergoing hemodialysis in Regional General Hospitalof Toto Kabila Hospital January 2017-October 2018. 43 patients were taken as samples by purposive sampling method that met the criteria. The data obtained were analyzed by univariate analysis.The results showed that the use of drugs in kidney failure patients undergoing hemodialysis in Regional General Hospitalof Toto Kabila Hospital in the period of January2017-October 2018 based on the four aspects were as follows: proper patient of 100%; proper drug of 86.05% and improper drug of 13.95%; proper indication of 83.72% and improper indication of 16.28%; proper dosage of 53.49%; and improper dosage of 46.51%.Overall, the drugs use evaluation results show that the drugs use on patients with Chronic Rena Failure undergoing hemodialysis in Regional General Hospitalof Toto Kabila Hospital in the period January 2017-October 2018 can be included in the good category.Keywords— Chronic Kidney Failure, Hemodialysis, Gorontalo